Positive electrode active material particles, method for producing positive electrode active material particles, and lithium ion secondary battery
By concentrating element M in the surface layer of O2 structured positive electrode active material particles, the method achieves high capacity and improved cycle characteristics in lithium-ion secondary batteries.
Patent Information
- Application Number
- JP2022143116
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-09-08
AI Technical Summary
Conventional positive electrode active substances with O2 structures face challenges in balancing high capacity and excellent cycle characteristics.
The method involves producing positive electrode active material particles with an O2 structure, where the molecular concentration of element M is higher in the surface layer than in the center, using a specific chemical composition and manufacturing process that includes ionizing NA-containing metal oxide particles with Li and doping element M on the surface.
This approach stabilizes the O2 structure, maintaining high capacity and improving cycle characteristics by concentrating element M in the surface layer, thereby enhancing the performance of lithium-ion secondary batteries.
Smart Images

Figure 0007622717000005 
Figure 0007622717000006 
Figure 0007622717000007
Abstract
Description
[Technical field]
[0001] The present application discloses positive electrode active material particles, a method for producing positive electrode active material particles, and a lithium ion secondary battery. [Background technology]
[0002] A positive electrode active material having an O2 type structure is known. As disclosed in Patent Document 1, a positive electrode active material having an O2 type structure is obtained by ion-exchanging at least a part of Na in a Na-containing transition metal oxide having a P2 type structure with Li. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-186937 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional positive electrode active materials having an O2-type structure have room for improvement in terms of achieving both high capacity and excellent cycle characteristics. [Means for solving the problem]
[0005] The present application discloses the following aspects as means for solving the above problems. <Aspect 1> Positive electrode active material particles, It has an O2 structure. Contains at least one element selected from Mn, Ni, and Co, Li, an element M, and O, The element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W; the molar concentration of the element M in the surface layer of the particle is higher than the molar concentration of the element M in the center of the particle; Positive electrode active material particles. <Aspect 2> The chemical composition of the whole particle is Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2 (where 0 < a ≤ 1.00, 0 ≤ b ≤ 0.20, x + y + z = 1, and 0 < p + q + r ≤ 0.07). The positive electrode active material particles of Aspect 1. <Aspect 3> The chemical composition in the surface layer part is Li a Na b Mn x-s Ni y-t Co z-u M s+t+u O2 (where 0 < a ≤ 1.00, 0 ≤ b ≤ 0.20, x + y + z = 1, and 0.08 < s + t + u). The positive electrode active material particles of Aspect 1 or 2. <Aspect 4> The chemical composition in the central part is Li a Na b Mn x-h Ni y-i Co z-j M h+i+j O2 (where 0 < a ≤ 1.00, 0 ≤ b ≤ 0.20, x + y + z = 1, and 0 ≤ h + i + j < 0.07). The positive electrode active material particles of any one of Aspects 1 to 3. <Aspect 5> A method for manufacturing positive electrode active material particles, comprising: Obtaining Na-containing transition metal oxide particles having a P2-type structure, and Ion-exchanging at least a part of Na in the Na-containing transition metal oxide particles with Li, and doping at least one element M selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W on the particle surface layer to obtain Li-containing transition metal oxide particles having an O2-type structure. A manufacturing method including the above. <Aspect 6> By bringing a salt containing Li and the element M into contact with the Na-containing transition metal oxide particles, at least a part of the Na in the Na-containing transition metal oxide particles is ion-exchanged with Li, and the element M is doped into the particle surface layer. The production method according to Aspect 5. <Aspect 7> The salt is a salt containing Li, the element M, and a halogen. The production method according to Aspect 6. <Aspect 8> The Na-containing transition metal oxide particles are Na c Mn x Ni y Co z having a chemical composition represented by O2 (where 0 < c ≦ 1.00 and x + y + z = 1). The production method according to any one of Aspects 5 to 7. <Aspect 9> A lithium-ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode. The positive electrode contains the positive electrode active material particles according to any one of Aspects 1 to 4. A lithium-ion secondary battery.
Advantages of the Invention
[0006] The positive electrode active material particles of the present disclosure are likely to achieve both high capacity and excellent cycle characteristics.
Brief Description of the Drawings
[0007] [Figure 1] Schematically shows the surface layer part and the central part of the positive electrode active material particles. [Diagram 2] Shows an example of the flow of the production method of the positive electrode active material particles. [Diagram 3] Schematically shows an example of the configuration of a lithium-ion secondary battery. [Figure 4] Shows the X-ray diffraction measurement results of the positive electrode active material particles according to Examples 1 and 2 and Comparative Examples 1 and 2. [Diagram 5] Shows the EDX element map of Al when observing the cross section of the positive electrode active material particles according to Example 1. [Figure 6] 1 shows an EDX elemental map of Al obtained when observing a cross section of a positive electrode active material particle according to Comparative Example 2. [Figure 7] 1 shows an example of an Al concentration distribution from one surface of a particle through the center to the other surface in an EDX elemental map of Al obtained by observing a cross section of a positive electrode active material particle according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] 1. Background A positive electrode active material having an O2 type structure is more stable in a high potential range than a conventional positive electrode active material (e.g., a positive electrode active material having an O3 type structure), and a large capacity can be obtained by utilizing charging and discharging in a high potential range. However, according to the inventor's new findings, a positive electrode active material having an O2 type structure is + When using a high potential above 4.4V (vs. Li / Li), the capacity degradation is the same as the conventional upper limit potential (for example, 4.4V (vs. Li / Li + Specifically, the capacity degradation is larger when the positive electrode active material with O2 structure is used at 4.7V (vs. Li / Li + ), the Lithium present between specific oxygen atoms in the O2-type structure is lost, destabilizing the O2-type structure and leading to a decrease in capacity.
[0009] In order to stabilize the O2 type structure, it is considered effective to dope the O2 type structure with element M such as Al. However, element M has a small contribution to charge and discharge, resulting in a decrease in charge and discharge capacity. In order to solve this, it is considered effective to concentrate element M in the surface layer of the particles. Since the positive electrode active material particles release Li from the surface layer of the particles in sequence during charging, Li is deficient in the surface layer of the particles, which tends to destabilize the O2 type structure, and it is considered that the priority of stabilizing the O2 type structure is higher in the surface layer of the particles than in the center of the particles, and it is also considered that if the O2 type structure can be stabilized in the surface layer of the particles, the effect will extend to the center.
[0010] However, in the prior art, it was difficult to concentrate the element M in the surface layer of the positive electrode active material particles having an O2 type structure. This is due to the constraints of the manufacturing process of the O2 type positive electrode active material particles. That is, as disclosed in Patent Document 1, in order to manufacture a positive electrode active material having an O2 type structure, it is necessary to first synthesize a Na-containing transition metal oxide having a P2 type structure, and then ion-exchange Na with Li to obtain a Li-containing transition metal oxide having an O2 type structure. On the other hand, when it is desired to concentrate a doping element in the surface layer of a positive electrode active material, it is common to form a core-shell structure consisting of a shell in which the doping element is concentrated and a core in which the doping element is dilute. Usually, the core-shell structure of the positive electrode active material is formed during precursor synthesis or calcination. Therefore, in the conventional common sense, it has been thought that in order to obtain an O2 type active material having a core-shell structure, it is necessary to form a core-shell structure when obtaining a Na-containing transition metal oxide having a P2 type structure. However, according to the inventor's findings, in such conventional methods, elements diffuse from the surface to the center of the particle and from the center to the surface due to the diffusion of elements associated with heating during sintering to obtain the P2 type structure, the diffusion of elements associated with structural phase transition during ion exchange, and the diffusion of elements associated with heating during ion exchange, making it difficult to concentrate the doping element in the surface layer of the particle.
[0011] In view of the above, the present inventors have conducted extensive research into a method for concentrating element M in the surface layer of positive electrode active material particles having an O2 type structure, and have found that element M can be appropriately concentrated in the surface layer of Li-containing transition metal oxide particles having an O2 type structure by obtaining Na-containing transition metal oxide particles having a P2 type structure and then doping them with element M when ion-exchanging Na with Li. In addition, the positive electrode active material particles produced in this manner have a low potential of, for example, 4.7 V (vs. Li / Li +It was also confirmed that the O2 type structure is stable even when used at high potentials of 1000V or more, the capacity is not easily reduced, and it is easy to achieve both high capacity and excellent cycle characteristics. Hereinafter, a description will be given of a positive electrode active material particle according to one embodiment, a method for producing the same, and a lithium ion secondary battery using the positive electrode active material particle.
[0012] 2. Positive electrode active material particles A positive electrode active material particle 1 according to one embodiment will be described with reference to FIG. 1. The positive electrode active material particle 1 has an O2 type structure. The positive electrode active material particle 1 contains at least one element selected from Mn, Ni, and Co, Li, an element M, and O. Here, the element M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W. In the positive electrode active material particle 1, the molar concentration of the element M in the surface layer portion 1a of the particle is higher than the molar concentration of the element M in the center portion 1b of the particle.
[0013] 2.1 Surface and central part In the present application, as shown in FIG. 1, the positive electrode active material particle 1 is described by dividing it into a surface layer 1a and a central portion 1b. The surface layer 1a of the positive electrode active material particle 1 refers to a portion from the particle surface to a predetermined depth, and the central portion 1b refers to a portion of the particle deeper than the surface layer 1a. The depth (thickness) of the surface layer 1a is not particularly limited. In the present application, the "surface layer" and the "central portion" of the positive electrode active material particle may be specified, for example, as follows. That is, when a cross section of the positive electrode active material is observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and an elemental analysis of the cross section is performed, if a core-shell structure consisting of a shell where element M is concentrated and a core where element M is thin can be confirmed, the shell is regarded as the "surface layer" and the core is regarded as the "central portion". On the other hand, if a clear core-shell structure is not confirmed with respect to the concentration distribution of element M, the surface layer and the central portion are distinguished as follows. That is, as shown in Fig. 1, a cross section of a positive electrode active material particle is observed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM) to obtain a two-dimensional image of the cross section of the positive electrode active material particle, and when the area of a region X from the surface of the positive electrode active material particle to a predetermined depth in the two-dimensional image is a1 and the area of the entire particle is a1+a2, the region X where a1 / (a1+a2) is 0.1 is regarded as the "surface layer portion of the positive electrode active material particle". By performing elemental analysis on the particle cross section for each of the "surface layer portion of the positive electrode active material particle" thus specified and the "center portion of the positive electrode active material particle" which is a deeper portion (portion toward the center), it is possible to determine whether the molar concentration of element M in the surface layer portion is higher than the molar concentration of element M in the center portion.
[0014] 2.2 Crystal structure The positive electrode active material particle 1 has at least an O2 type structure (belonging to space group P63mc) as a crystal structure. The positive electrode active material particle 1 may have an O2 type structure and a crystal structure other than the O2 type structure. Examples of crystal structures other than the O2 type structure include a T♯2 type structure (belonging to space group Cmca) formed when Li is deintercalated from the O2 type structure and an O6 type structure (belonging to space group R-3m, with a c-axis length of 2.5 nm to 3.5 nm, typically 2.9 nm to 3.0 nm, different from the O3 type structure also belonging to space group R-3m). The positive electrode active material particle 1 may have an O2 type structure as a main phase, or may have a crystal structure other than the O2 type structure as a main phase, but is particularly preferably an O2 type structure as a main phase. The positive electrode active material particle 1 may have a crystal structure that is a main phase that changes depending on the charge / discharge state.
[0015] 2.3 Chemical composition The positive electrode active material particle 1 contains at least one element selected from Mn, Ni, and Co, Li, element M, and O as constituent elements. In particular, when the positive electrode active material particle 1 contains at least Mn, at least one of Ni and Co, Li, and O as constituent elements, and especially when the positive electrode active material particle 1 contains at least Li, Mn, Ni, Co, and O as constituent elements, it is easy to ensure higher performance. However, the positive electrode active material particle 1 may, for example, release Li almost completely upon charging, and the molar concentration of Li may approach 0 to the limit. In addition, the positive electrode active material particle 1 may contain Na as a constituent element due to the manufacturing process described later. In addition, the positive electrode active material particle 1 may contain other impurity elements.
[0016] In the positive electrode active material particle 1, the O2 type structure can be stabilized by containing a specific element M. Specifically, by containing an element M whose valence is unlikely to change in the positive electrode active material particle 1, even if Li is desorbed from the positive electrode active material particle 1 by charging, Li is present around the element M. +is likely to remain, and this can stabilize the O2 type structure. The element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W. In particular, when the positive electrode active material particle 1 contains at least one selected from Al, Ga, Mg, Ti, Cr, Nb, and Mo as the element M, and further contains at least one of Al and Ga, particularly when it contains Al, the O2 type structure is more likely to be stabilized. In addition, when Al or Ga is adopted as the element M, it is also possible to greatly lower the ion exchange temperature (Li substitution temperature and element M doping temperature) in step S2 in the manufacturing method described later.
[0017] In the positive electrode active material particles having an O2 type structure, it is considered that the higher the molar concentration of element M, the more the O2 type structure can be stabilized. On the other hand, since element M has a small contribution to charge and discharge, it is considered that the lower the molar concentration of element M, the more the charge and discharge capacity can be improved. In this respect, in the positive electrode active material particles 1 of the present disclosure, in order to suppress the decrease in charge and discharge capacity due to element M while ensuring the stabilization effect of element M on the O2 type structure, element M is concentrated in the surface layer portion 1a of the particle. In other words, in the positive electrode active material particles 1 of the present disclosure, the molar concentration of element M in the surface layer portion 1a of the particle is higher than the molar concentration of element M in the central portion 1b of the particle. As described above, according to the positive electrode active material particles 1, the stabilization effect of the O2 type structure is ensured by concentrating element M in the surface layer portion 1a, and a high charge and discharge capacity is ensured by reducing the amount of element M in the central portion 1b.
[0018] In the present application, the "molar concentration of element M in the surface layer of the particle" means the "average molar concentration" of element M contained in the surface layer of the particle, and the "molar concentration of element M in the central part of the particle" means the "average molar concentration" of element M contained in the central part of the particle. That is, in the positive electrode active material particle 1, as long as the "average molar concentration" of each of the surface layer part 1a and the central part 1b is such that the molar concentration of element M in the surface layer part 1a is higher than the molar concentration of element M in the central part 1b, the dispersion state of element M in each of the surface layer part 1a and the central part 1b is not particularly limited. That is, in the surface layer part 1a, element M may be uniformly dispersed or non-uniformly dispersed. Further, in the central part 1b, element M may be uniformly dispersed, non-uniformly dispersed, or element M may not be present. Further, in the positive electrode active material particle 1, the molar concentration of element M may change continuously, intermittently, or irregularly from the surface to the center of the particle. In particular, when the positive electrode active material particle 1 has a core-shell structure in which the surface layer part 1a in which element M is relatively concentrated is a shell and the central part 1b in which element M is relatively small or substantially does not contain element M is a core, a higher effect is more easily obtained.
[0019] The positive electrode active material particle 1 contains at least one element selected from Mn, Ni, and Co, Li, element M, and O. The composition ratio of each element is not particularly limited as long as the O2 type structure can be maintained. The positive electrode active material particle 1 can have various chemical compositions. Hereinafter, an example of the chemical composition will be described.
[0020] The chemical composition of the entire positive electrode active material particle 1 (average chemical composition of the entire particle) may be represented by Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2 (where 0 < a ≤ 1.00, 0 ≤ b ≤ 0.20, x + y + z = 1, and 0 < p + q + r ≤ 0.07).
[0021] In the above chemical composition of the particle as a whole, a may be greater than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, or 0.7 or less. b may be greater than 0 or greater than 0, and may be 0.15 or less, 0.10 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, or 0.01 or less. x may be greater than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. In addition, y may be 0 or more, 0.1 or more, or 0.2 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. In addition, z may be 0 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less.
[0022] As described above, element M has a small contribution to charge and discharge. In this regard, in the chemical composition of the particle as a whole, p+q+r is 0.07 or less, so that a high charge and discharge capacity is easily ensured. p+q+r may be 0.06 or less, 0.05 or less, or 0.04 or less. On the other hand, as described above, the inclusion of element M provides a stabilizing effect on the O2 type structure. In this regard, in the chemical composition of the particle as a whole, p+q+r may be more than 0, and may be 0.01 or more, 0.02 or more, or 0.03 or more.
[0023] The composition of O is approximately 2, but is not necessarily exactly 2.0 and is variable.
[0024] In addition, in the chemical composition of the entire positive electrode active material particles 1, when the valence of element M is +n, the relationship 3.0 ≦ 4(x - p) + 2(y - q) + 3(z - r) + n(p + q + r) ≦ 3.5 may be satisfied. This is intended to be in a range where the total valence of the metal in the positive electrode active material is close to 3.33 valences (charge neutrality when a is 0.67). As will be described later, the positive electrode active material having an O2-type structure passes through a Na-containing transition metal oxide having a P2-type structure during its synthesis. When the Na composition at this time is in the range of 0.5 or more and 1.0 or less, charge neutrality is achieved, which corresponds to the case where the above relationship is satisfied.
[0025] The chemical composition (average chemical composition in the surface layer portion 1a) of the surface layer portion 1a of the positive electrode active material particles 1 may be represented by Li a Na b Mn x-s Ni y-t Co z-u M s+t+u O2 (where 0 < a ≦ 1.00, 0 ≦ b ≦ 0.20, x + y + z = 1, and 0.08 < s + t + u).
[0026] In the chemical composition of the surface layer portion 1a, a may be greater than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, or 0.7 or less. b may be greater than 0 or greater than 0, and may be 0.15 or less, 0.10 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, or 0.01 or less. x may be greater than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. In addition, y may be 0 or more, 0.1 or more, or 0.2 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. In addition, z may be 0 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less.
[0027] As described above, in the positive electrode active material particle 1, the molar concentration of element M in the surface layer portion 1a is increased in order to enhance the stabilization effect of the O2 type structure. Specifically, when Li is desorbed from the positive electrode active material particle by charging, the element M, whose valence is unlikely to change, is contained, and Li is present around the element M. + The remaining Li is the Li closest to element M, which stabilizes the O2 structure. + Take the site. This remaining Li + In order for the structural stabilization effect of the Li to be exerted on the entire shell, the remaining Li + The second nearest neighbor Li + By the time the position was reached, another remaining Li +It is preferable that there is [such a situation]. Therefore, when the element M is uniformly distributed, it is considered that the structure stabilization effect is exhibited throughout the shell part when another element M exists at the second-nearest metal positions of all the element M. Since the number of the first- and second-nearest metal positions of the element M is 12, the minimum amount of s + t + u required for another element M to exist up to the second-nearest metal position is 1 / 12 ≒ 0.08. In this regard, in the chemical composition of the surface layer part 1a described above, when s + t + u exceeds 0.08, it is easier to ensure a more excellent stabilization effect. s + t + u may be 0.09 or more, or 0.10 or more. On the other hand, the stabilization effect of the O2-type structure by the element M saturates when the molar concentration of the element M becomes a certain level or more. In this regard, in the chemical composition of the surface layer part 1a described above, s + t + u may be 0.15 or less, 0.14 or less, 0.13 or less, or 0.12 or less.
[0028] The composition of O is approximately 2, but it is not necessarily exactly 2.0 and is indefinite.
[0029] The chemical composition (average chemical composition in the central part 1b) in the central part 1b of the positive electrode active material particles 1 is Li a Na b Mn x-h Ni y-i Co z-j M h+i+j O2 (where 0 < a ≦ 1.00, 0 ≦ b ≦ 0.20, x + y + z = 1, and 0 ≦ h + i + j < 0.07).
[0030] In the chemical composition of the central portion 1b, a may be greater than 0, 0.1 or greater, 0.2 or greater, 0.3 or greater, 0.4 or greater, 0.5 or greater, or 0.6 or greater, and may be 1.0 or less, 0.9 or less, 0.8 or less, or 0.7 or less. b may be greater than 0 or greater, and may be 0.15 or less, 0.10 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, or 0.01 or less. x may be greater than 0, 0.1 or greater, 0.2 or greater, 0.3 or greater, 0.4 or greater, or 0.5 or greater, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. In addition, y may be 0 or more, 0.1 or more, or 0.2 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. In addition, z may be 0 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less.
[0031] As described above, in order to ensure a high charge / discharge capacity, the molar concentration of element M is low in the central portion 1b. In this regard, in the chemical composition of the central portion 1b, when h+i+j is less than 0.07, a higher charge / discharge capacity is likely to be ensured. h+i+j may be 0.06 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, or 0.01 or less. On the other hand, as described above, even if the central portion 1b does not contain the element M, the structure of the central portion 1b is likely to be kept stable due to the structure stabilization effect of the surface layer portion 1a. In this regard, in the chemical composition of the central portion 1b, h+i+j may be 0, 0 or more, or more than 0.
[0032] The composition of O is approximately 2, but is not necessarily exactly 2.0 and is variable.
[0033] 2.4 Particle Shape The positive electrode active material particles 1 may be solid particles, hollow particles, or particles having voids. The positive electrode active material particles 1 may be primary particles, or secondary particles formed by agglomeration of a plurality of primary particles. It is preferable that each of the primary particles of the positive electrode active material particles 1 has the above-mentioned chemical composition. The average particle diameter (D50) of the positive electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. The average particle diameter D50 in the present application is the particle diameter (median diameter) at an integrated value of 50% in a volume-based particle size distribution obtained by a laser diffraction / scattering method.
[0034] 3. Method for producing positive electrode active material particles As described above, the positive electrode active material particle 1 having the O2 type structure can be produced by obtaining a Na-containing transition metal oxide particle having a P2 type structure, and then ion-exchanging at least a part of Na with Li and doping with element M. That is, as shown in FIG. 2, the method for producing the positive electrode active material particle 1 according to one embodiment includes the following steps: Step S1: Obtaining Na-containing transition metal oxide particles having a P2 type structure, and Step S2: ion-exchanging at least a portion of the Na in the Na-containing transition metal oxide particles with Li, and doping the particle surface with at least one element M selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W to obtain Li-containing transition metal oxide particles having an O2 type structure; Includes.
[0035] 3.1 Process S1 In step S1, Na-containing transition metal oxide particles having a P2 type structure are obtained.
[0036] Since the O2 type structure is a metastable phase, it is necessary to first synthesize a Na-containing transition metal oxide having a similar P2 type structure, and then ion-exchange at least a part of the Na in the Na-containing transition metal oxide with Li to obtain the O2 type structure. Therefore, in the manufacturing method of the present disclosure, first, Na-containing transition metal oxide particles having a P2 type structure are obtained. The Na-containing transition metal oxide having a P2 type structure can be synthesized by a known method. In step S1, for example, a precipitate (precursor particle) is obtained using an ion source capable of forming a precipitate in an aqueous solution with transition metal ions and a transition metal source, and then the precipitate and a Na source are mixed to obtain a mixture, and the mixture is optionally shaped and pre-fired, and then fired, whereby the Na-containing transition metal oxide having a P2 type structure can be synthesized.
[0037] In step S1, examples of the ion source capable of forming a precipitate with the transition metal ion include salts such as carbonates and nitrates, sodium hydroxide, and sodium oxide. Examples of the transition metal source include salts such as nitrates, sulfates, and carbonates, and hydroxides. In step S1, the ion source and the transition metal source may be prepared as solutions, and the solutions may be added dropwise and mixed to obtain a precipitate. In this case, various sodium compounds may be used as a base, and an aqueous ammonia solution or the like may be added to adjust the basicity. More specifically, in step S1, a salt containing at least one transition metal element selected from Mn, Ni, and Co may be obtained as the precipitate. The precipitate may be at least one of carbonates, sulfates, nitrates, acetates, and hydroxides. Specifically, the precipitate may be a salt represented by MeCO3 (Me is at least one transition metal element selected from Mn, Ni, and Co), a salt represented by MeSO4, a salt represented by Me(NO3)2, a salt represented by Me(CH3COO)2, or a compound represented by Me(OH)2. The precipitate may be obtained by a solution method such as a coprecipitation method or a sol-gel method. Specifically, in the case of the coprecipitation method, an aqueous solution of MeSO4 and an aqueous solution of Na2CO3 are prepared, and each aqueous solution is dropped and mixed to obtain a precipitate.
[0038] In step S1, the amount of the Na source mixed with the precipitate may be determined taking into consideration the amount of Na lost during the subsequent firing. As the Na source, for example, a Na salt such as a carbonate or sulfate, or a Na compound such as sodium oxide or sodium hydroxide may be used. In step S1, the surface of the above precipitate (precursor particle) may be coated with a Na salt to obtain a coated particle. Here, the coated particle may be obtained by coating at least a part of the surface of the above precursor particle with a Na salt. The coated particle may be obtained by coating 40 area% or more, 50 area% or more, 60 area% or more, or 70 area% of the surface of the above precursor particle with a Na salt.
[0039] In step S1, the pre-firing is performed at a temperature equal to or lower than that of the main firing. For example, the pre-firing can be performed at a temperature equal to or lower than 600° C. The pre-firing time is not particularly limited. The pre-firing may be omitted.
[0040] In step S1, the main firing may be performed at a temperature of, for example, 700°C or higher and 1100°C or lower. It is preferably 800°C or higher and 1000°C or lower. If the main firing temperature is too low, Na doping is not performed, and if the main firing temperature is too high, an O3 type structure is likely to be formed instead of a P2 type structure. The main firing time is not particularly limited, and may be, for example, 30 minutes or longer and 10 hours or shorter. The main firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere such as air atmosphere or an inert gas atmosphere.
[0041] The Na-containing transition metal oxide particles obtained by step S1 contain, for example, as constituent elements, at least one element selected from Mn, Ni, and Co, Na, and O. In particular, when the constituent elements contain at least Na, Mn, at least one of Ni and Co, and O, and especially when the constituent elements contain at least Na, Mn, Ni, Co, and O, the performance of the positive electrode active material particles is likely to be further improved. More specifically, the Na-containing transition metal oxide particles obtained by step S1 contain Na c Mn xNi y Co z It may also have a chemical composition represented by O2 (where 0 < c ≤ 1.00 and x + y + z = 1). When the Na-containing transition metal oxide particles have such a chemical composition, the P2-type structure is likely to be maintained. In the above chemical composition, c may be greater than 0, 0.10 or more, 0.20 or more, 0.30 or more, 0.40 or more, 0.50 or more, or 0.60 or more, and may also be 1.00 or less, 0.90 or less, 0.80 or less, or 0.70 or less. Also, x may be 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. Also, y may be 0 or more, 0.1 or more, or 0.2 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. Also, z may be 0 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. The composition of O is approximately 2, but is not necessarily exactly 2.0 and is indefinite.
[0042] 3.2 Step S2 In Step S2, at least a part of the Na in the Na-containing transition metal oxide particles obtained as described above is ion-exchanged with Li, and the element M is doped on the particle surface layer to obtain Li-containing transition metal oxide particles having an O2-type structure.
[0043] In step S2, for example, by ion exchange using a lithium salt, at least a part of Na in the Na-containing transition metal oxide particles is replaced with Li. There are two methods for ion exchange: a method using an aqueous solution containing a lithium salt, and a method using a molten salt obtained by heating and melting a lithium salt. From the viewpoint that the P2 type structure is easily broken by the penetration of water and from the viewpoint of crystallinity, the method using a molten salt is preferable among the above two methods. That is, by mixing the Na-containing transition metal oxide particles having the above-mentioned P2 type structure with the molten salt and heating to a temperature equal to or higher than the melting point of the molten salt, at least a part of Na can be replaced with Li by ion exchange. For example, lithium halide can be used as the lithium salt constituting the molten salt. The lithium halide is preferably at least one of lithium chloride, lithium bromide, and lithium iodide.
[0044] In step S2, during the ion exchange, the element M is doped into the particle surface layer. For example, the element M can be doped into the particle surface layer by contacting the particle with an aqueous solution containing the element M, or by contacting the particle with a molten salt obtained by heating and melting a salt containing the element M. Of the above two methods, the method using a molten salt is preferred from the viewpoint that the P2 type structure is easily broken by the penetration of water and from the viewpoint of crystallinity. That is, the element M can be doped into the particle surface layer by mixing the Na-containing transition metal oxide particles having the above-mentioned P2 type structure with the molten salt and heating the mixture to a temperature equal to or higher than the melting point of the molten salt. Examples of the salt containing the element M constituting the molten salt include halides of the element M.
[0045] In step S2, the Na-containing transition metal oxide particles may be contacted with a salt containing Li and element M to ion-exchange at least a part of the Na in the Na-containing transition metal oxide particles with Li, and to dope the particle surface with the element M. In this way, when a salt containing Li and element M (a mixed salt of a lithium salt and a salt of element M, or a composite salt of Li and element M) is used, the melting point of the salt may be lower than when a lithium salt or a salt of element M is used alone. In particular, when a salt containing at least one of Al and Ga and Li is used as element M, the melting point is likely to be significantly lowered. That is, the temperature required for melting is lowered, and the ion exchange of Li and the doping of element M can be performed at a low temperature. The mixing ratio of the lithium salt and the salt of element M is not particularly limited, but the melting point tends to be higher when the ratio of the lithium salt is high. Specific examples of salts containing Li and element M include salts containing Li, element M, and a halogen (a mixed salt of lithium halide and a halide of element M, or a complex halide of Li and element M).
[0046] The temperature in step S2 (for example, the heating temperature when the Na-containing transition metal oxide particles are contacted with a salt containing Li and element M and then heated to perform ion exchange) may be, for example, 600°C or less, 500°C or less, 400°C or less, 350°C or less, 300°C or less, 280°C or less, 250°C or less, 230°C or less, 200°C or less, 170°C or less, or 150°C or less, and may be room temperature or higher or 100°C or higher. If the temperature is too high, the stable phase O3 type structure is likely to be formed instead of the O2 type structure. In addition, when an aqueous solution containing a salt is used, it is considered that ion exchange of Li and doping of element M are possible even at room temperature. On the other hand, when a molten salt is used, ion exchange of Li and doping of element M are performed at a temperature above the melting point of the molten salt as described above. From the viewpoint of shortening the time required for step S2, the temperature in step S2 may be 100°C or higher.
[0047] The time in step S2 (for example, the heating time when the Na-containing transition metal oxide particles are brought into contact with a salt containing Li and the element M and then heated to perform ion exchange) may be adjusted so that most of the Na in the Na-containing transition metal oxide particles is replaced with Li and the element M is doped into the particle surface layer. If the heating time is too long, there is a risk that the element M will diffuse to the center of the particle. Even if the element M diffuses to the center of the particle, it is considered possible to ensure a molar concentration difference of the element M between the surface layer and the center of the particle. From the viewpoint of ensuring a sufficient time for the salt containing Li and the element M to melt, from the viewpoint of making the molar concentration of the element M in the center as low as possible, and from the viewpoint of easily forming a shell in which the element M is concentrated in the surface layer, the time in step S2 may be, for example, 10 minutes or more or 60 minutes or more, and may be 12 hours or less or 6 hours or less.
[0048] The atmosphere in step S2 is not particularly limited, and may be, for example, an oxygen-containing atmosphere such as air atmosphere, or an inert gas atmosphere.
[0049] After step S2, the Li-containing transition metal oxide particles may be subjected to some post-treatment such as washing. The positive electrode active material particles produced through the above steps S1 and S2 have an O2 type structure and contain at least one element selected from Mn, Ni, and Co, Li, element M, and O, where the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W, and the molar concentration of the element M in the surface layer of the particle is higher than the molar concentration of the element M in the center of the particle.
[0050] 4.Positive electrode The technology of the present disclosure also has an aspect as a positive electrode. That is, the positive electrode of the present disclosure has an O2 type structure as a positive electrode active material particle, and contains at least one element selected from Mn, Ni and Co, Li, element M, and O, and the element M is at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo and W, and the molar concentration of the element M in the surface layer part of the particle is higher than the molar concentration of the element M in the center part of the particle. As shown in FIG. 3, a positive electrode 10 according to one embodiment may include a positive electrode active material layer 11 and a positive electrode current collector 12, and in this case, the positive electrode active material layer 11 may include the above-mentioned positive electrode active material particle 1.
[0051] 4.1 Cathode active material layer The positive electrode active material layer 11 includes at least the positive electrode active material particles 1 as the positive electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the positive electrode active material layer 11 may further include various additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 11 may be appropriately determined according to the target battery performance. For example, the content of the positive electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, assuming that the entire positive electrode active material layer 11 (total solid content) is 100 mass%. The shape of the positive electrode active material layer 11 is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer 11 having a substantially flat surface. The thickness of the positive electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0052] 4.1.1 Cathode active material The positive electrode active material layer 11 may contain only the positive electrode active material particles 1 as the positive electrode active material. Alternatively, the positive electrode active material layer 11 may contain, in addition to the positive electrode active material particles 1, a different type of positive electrode active material (another positive electrode active material). From the viewpoint of further enhancing the effect of the technology of the present disclosure, the content of the other positive electrode active material in the positive electrode active material layer 11 may be small. For example, the content of the positive electrode active material particles 1 may be 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more, where the total positive electrode active material contained in the positive electrode active material layer 11 is taken as 100 mass%.
[0053] The surface of the positive electrode active material may be covered with a protective layer containing a lithium ion conductive oxide. That is, the positive electrode active material layer 11 may include a composite having the above-mentioned positive electrode active material particle 1 and a protective layer provided on the surface thereof. This makes it easier to suppress the reaction between the positive electrode active material particle 1 and a sulfide (for example, a sulfide solid electrolyte described later). Examples of lithium ion conductive oxides include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, and Li2WO4. The coverage (area ratio) of the protective layer may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.
[0054] 4.1.2 Electrolytes The electrolyte that can be contained in the positive electrode active material layer 11 may be a solid electrolyte, a liquid electrolyte (electrolytic solution), or a combination thereof.
[0055] The solid electrolyte may be any known solid electrolyte for lithium ion secondary batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes are excellent in ion conductivity and heat resistance. Examples of inorganic solid electrolytes include lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-X Examples of the oxide solid electrolyte include (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass; and sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. In particular, sulfide solid electrolytes, particularly sulfide solid electrolytes containing at least Li, S, and P as constituent elements, have high performance. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, particulate. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.
[0056] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be an aqueous electrolyte or a non-aqueous electrolyte. The composition of the electrolyte may be the same as that of the electrolyte of a lithium ion secondary battery. For example, the electrolyte may be a carbonate-based solvent in which a lithium salt is dissolved at a predetermined concentration. Examples of the carbonate-based solvent include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of the lithium salt include LiPF6.
[0057] 4.1.3 Conductive additives Examples of the conductive assistant that may be included in the positive electrode active material layer 11 include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.
[0058] 4.1.4 Binders Examples of binders that can be included in the positive electrode active material layer 11 include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.
[0059] 4.2 Positive electrode current collector As shown in FIG. 3, the positive electrode 10 may include a positive electrode collector 12 in contact with the positive electrode active material layer 11. The positive electrode collector 12 may be any of those commonly used as a positive electrode collector for a battery. The positive electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The positive electrode collector 12 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 12 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 12 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode collector 12 may contain Al. The positive electrode collector 12 may have some kind of coating layer on its surface for the purpose of adjusting resistance, or the like. The positive electrode current collector 12 may be a metal foil or a substrate plated or vapor-deposited with the above metal. When the positive electrode current collector 12 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the positive electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0060] 4.3 Other In addition to the above configuration, the positive electrode 10 may have a general configuration as a positive electrode of a lithium ion secondary battery. For example, a tab, a terminal, etc. The positive electrode 10 can be manufactured by a known method except that the above positive electrode active material particles 1 are used as the positive electrode active material. For example, the positive electrode active material layer 11 can be easily formed by forming a positive electrode mixture containing the above various components in a dry or wet manner. The positive electrode active material layer 11 may be formed together with the positive electrode current collector 12 or may be formed separately from the positive electrode current collector 12.
[0061] 5. Lithium-ion secondary batteries As shown in Fig. 3, a lithium ion secondary battery 100 according to one embodiment has a positive electrode 10, an electrolyte layer 20, and a negative electrode 30. Here, the positive electrode 10 includes the positive electrode active material particles 1 of the present disclosure. As described above, the positive electrode active material particles 1 tend to achieve both high charge / discharge capacity and excellent cycle characteristics. In this regard, the performance of the lithium ion secondary battery 100 is likely to be improved by including the positive electrode active material particles 1 in the positive electrode 10 of the lithium ion secondary battery 100. A specific configuration example of the positive electrode 10 is as described above.
[0062] 5.1 Electrolyte layer The electrolyte layer 20 contains at least an electrolyte. When the lithium ion secondary battery 100 is a solid-state battery (a battery containing a solid electrolyte, which may be a battery partially using a liquid electrolyte in combination, or an all-solid-state battery not containing a liquid electrolyte), the electrolyte layer 20 contains a solid electrolyte and may further contain a binder or the like. In this case, the content of the solid electrolyte and the binder or the like in the electrolyte layer 20 is not particularly limited. On the other hand, when the lithium ion secondary battery 100 is an electrolyte battery, the electrolyte layer 20 contains an electrolyte solution and may further have a separator or the like for holding the electrolyte solution and preventing contact between the positive electrode active material layer 11 and the negative electrode active material layer 31. The thickness of the electrolyte layer 20 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0063] The electrolyte contained in the electrolyte layer 20 may be appropriately selected from those exemplified as electrolytes that may be contained in the positive electrode active material layer described above. The binder that may be contained in the electrolyte layer 20 may also be appropriately selected from those exemplified as binders that may be contained in the positive electrode active material layer described above. The electrolyte and the binder may each be used alone or in combination of two or more. The separator may be any separator that is normally used in lithium ion secondary batteries, and examples of the separator include those made of resins such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.
[0064] 5.2 Negative electrode As shown in FIG. 3, the negative electrode 30 may include a negative electrode active material layer 31 and a negative electrode current collector 32.
[0065] 5.2.1 Negative electrode active material layer The negative electrode active material layer 31 includes at least a negative electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the negative electrode active material layer 31 may further include various additives. The contents of the negative electrode active material, electrolyte, conductive assistant, binder, and the like in the negative electrode active material layer 31 may be appropriately determined according to the intended battery performance. For example, the content of the negative electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, with the entire negative electrode active material layer 31 (total solid content) being 100 mass%. The shape of the negative electrode active material layer 31 is not particularly limited, and may be, for example, a sheet-like negative electrode active material layer having a substantially flat surface. The thickness of the negative electrode active material layer 31 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.
[0066] As the negative electrode active material, various substances having a potential (charge / discharge potential) for absorbing and releasing lithium ions that is lower than that of the positive electrode active material particles 1 having the above-mentioned O2 type structure can be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, and the like can be used. Only one type of negative electrode active material may be used alone, or two or more types may be used in combination.
[0067] The shape of the negative electrode active material may be any shape that is common for a negative electrode active material of a battery. For example, the negative electrode active material may be in a particulate form. The negative electrode active material particles may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in a sheet form (foil form, film form) such as lithium foil. That is, the negative electrode active material layer 31 may be made of a sheet of the negative electrode active material.
[0068] Examples of the electrolyte that can be contained in the negative electrode active material layer 31 include the above-mentioned solid electrolyte, electrolytic solution, or a combination thereof. Examples of the conductive assistant that can be contained in the negative electrode active material layer 31 include the above-mentioned carbon material and metal material. The binder that can be contained in the negative electrode active material layer 31 may be appropriately selected from, for example, those exemplified as the binder that can be contained in the above-mentioned positive electrode active material layer 11. Only one type of electrolyte or binder may be used alone, or two or more types may be used in combination.
[0069] 5.2.2 Negative electrode current collector As shown in FIG. 3, the negative electrode 30 may include a negative electrode current collector 32 in contact with the negative electrode active material layer 31. The negative electrode current collector 32 may be any of those commonly used as a negative electrode current collector for a battery. The negative electrode current collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The negative electrode current collector 32 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 32 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 32 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 32 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 32 may have some kind of coating layer on its surface for the purpose of adjusting the resistance or the like. The negative electrode current collector 32 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. When the negative electrode current collector 32 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.
[0070] 5.3 Other matters The lithium ion secondary battery 100 may have the above-mentioned components housed inside an exterior body. Any known exterior body for a battery can be used as the exterior body. A plurality of batteries 100 may be electrically connected and stacked in any manner to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. The lithium ion secondary battery 100 may also have other obvious components such as necessary terminals. The shape of the lithium ion secondary battery 100 may be, for example, a coin type, a laminate type, a cylindrical type, a square type, or the like.
[0071] The lithium ion secondary battery 100 can be manufactured by applying a known method. For example, it can be manufactured as follows. However, the manufacturing method of the lithium ion secondary battery 100 is not limited to the following method, and each layer may be formed by, for example, dry molding or the like. (1) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The negative electrode layer slurry is then applied to the surface of a negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, thereby forming a negative electrode. (2) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used. The positive electrode layer slurry is then applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, thereby forming a positive electrode. (3) The layers are laminated so that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a laminate having the negative electrode current collector, the negative electrode active material layer, the electrolyte layer, the positive electrode active material layer, and the positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case, and in the case of an electrolyte battery, the battery case is filled with electrolyte, and the laminate is immersed in the electrolyte and sealed in the battery case to form a secondary battery. In the case of an electrolyte battery, the electrolyte may be impregnated in the negative electrode active material layer, the separator, and the positive electrode active material layer at the above step (3).
[0072] 6. Battery System The technology of the present disclosure also has an aspect of a system for controlling the charging and discharging of a lithium ion secondary battery. That is, the battery system of the present disclosure includes the lithium ion secondary battery 100 of the present disclosure and a control unit (not shown) that controls the charging and discharging of the lithium ion secondary battery 100, and the control unit controls the positive electrode potential at the end-of-charge potential of the lithium ion secondary battery 100 to be 4.7 V (vs. Li / Li + ) or higher, preferably 4.8V (vs. Li / Li + ) or higher. As described above, the positive electrode active material particles 1 of the present disclosure are unlikely to cause cation mixing even when used in a high potential region, and destabilization of the O2 type structure can be suppressed. For example, the positive electrode active material particles 1 of the present disclosure can be used at a potential of 4.8 V (vs. Li / Li) at which almost all of Li is extracted. + ), stable charging and discharging is possible with almost no cation mixing occurring. The control unit may be any unit capable of controlling the charging and discharging of the lithium ion secondary battery 100 as described above. When the control unit controls the charging and discharging of the lithium ion secondary battery 100, the positive electrode potential at the discharge end potential of the lithium ion secondary battery 100 is not particularly limited, and may be determined according to the desired battery performance.
[0073] 7. Method for charging and discharging a lithium-ion secondary battery, method for improving the charge and discharge capacity of a lithium-ion secondary battery, and method for improving the cycle characteristics of a lithium-ion secondary battery The technology of the present disclosure also has an aspect of a method for charging and discharging a lithium ion secondary battery, a method for improving the charge and discharge capacity of a lithium ion secondary battery, and a method for improving the cycle characteristics of a lithium ion secondary battery. That is, the method for charging and discharging a lithium ion secondary battery of the present disclosure includes charging or discharging the lithium ion secondary battery while using the positive electrode active material particles of the present disclosure in the positive electrode of the lithium ion secondary battery, and the positive electrode potential at the end of charge is 4.7 V (vs. Li / Li + ) or higher, preferably 4.8V (vs. Li / Li + The charging of the lithium ion secondary battery is controlled so that the charge / discharge capacity of the lithium ion secondary battery is equal to or greater than the above-mentioned value. The method for improving the charge / discharge capacity of the lithium ion secondary battery according to the present disclosure, or the method for improving the cycle characteristics of the lithium ion secondary battery according to the present disclosure, is characterized in that the positive electrode active material particles according to the present disclosure are used in the positive electrode of the lithium ion secondary battery.
[0074] 8. Vehicles equipped with lithium-ion secondary batteries As described above, when the positive electrode active material particles of the present disclosure are contained in the positive electrode of a lithium ion secondary battery, the lithium ion secondary battery is expected to have a high capacity and improved cycle characteristics. A lithium ion secondary battery having such excellent performance can be suitably used in at least one vehicle selected from, for example, a hybrid vehicle (HEV), a plug-in hybrid vehicle (PHEV), and an electric vehicle (BEV). That is, the technology of the present disclosure also has an aspect of a vehicle having a lithium ion secondary battery, the lithium ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode, and the positive electrode containing the positive electrode active material particles of the present disclosure. EXAMPLES
[0075] As described above, one embodiment of the positive electrode active material particles, the method for producing the positive electrode active material particles, and the lithium ion secondary battery of the present disclosure has been described, but the positive electrode active material particles, the method for producing the positive electrode active material particles, and the lithium ion secondary battery of the present disclosure can be modified in various ways other than the above embodiment without departing from the gist of the present disclosure. Below, the technology of the present disclosure will be described in more detail while showing examples, but the technology of the present disclosure is not limited to the following examples.
[0076] 1. Preparation of positive electrode active material particles and coin cells for evaluation 1.1 Example 1 1.1.1 Preparation of precipitates (precursor particles) Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, and Co(NO3)2·6H2O were dissolved in pure water so that the molar ratio of Mn, Ni, and Co was 5:2:3 to obtain the first solution. Meanwhile, a second solution containing 12 wt% Na2CO3 was prepared. The first and second solutions were titrated simultaneously into a beaker. At this time, the titration speed was controlled so that the pH was 7.0 or more and less than 7.1. After the titration was completed, the mixed solution was stirred at 50°C and 300 rpm for 24 hours. The obtained reaction product was washed with pure water, and only the precipitate was separated by centrifugation. The obtained precipitate was dried at 120°C for 48 hours, and then crushed in an agate mortar to obtain precursor particles.
[0077] 1.1.2 Preparation of Na-containing transition metal oxide particles with P2-type structure The precursor particles and Na2CO3 are mixed in a mixture having a composition ratio of Na 0.67 Mn 0.5 Ni 0.2 Co 0.3 The mixture was mixed so that the mixture was O2, and a mixed powder was obtained. The mixed powder obtained was pressed with a load of 2 tons by cold isostatic pressing to produce pellets. The obtained pellets were pre-fired at 600°C for 6 hours in an air atmosphere, and then fired at 900°C for 24 hours to obtain Na-containing transition metal oxide particles with a P2 type structure.
[0078] 1.1.3 Preparation of positive electrode active material particles AlCl3 and LiCl were mixed in a molar ratio of 1:1 to obtain a mixed salt. The obtained mixed salt and the above-mentioned Na-containing transition metal oxide particles were weighed out so that the amount of Li contained in the mixed salt was twice the amount of Na contained in the Na-containing transition metal oxide particles. The mixed salt and the Na-containing transition metal oxide particles were mixed and ion-exchanged for 1 h at 150°C in an air atmosphere. After the ion-exchange, water was added to dissolve the salt, and the mixture was further washed with water to obtain Li-containing transition metal oxide particles having an O2 type structure. The obtained Li-containing transition metal oxide particles were crushed by a ball mill to obtain the target substance, positive electrode active material particles.
[0079] 1.1.4 Preparation of the positive electrode 85 g of the positive electrode active material particles and 10 g of carbon black were added to 125 mL of n-methylpyrrolidone solution in which 5 g of polyvinylidene fluoride (PVdF) was dissolved, and the mixture was kneaded uniformly to prepare a paste. This paste was applied to an Al foil with a thickness of 15 μm in a coating weight of 6 mg / cm. 2 The laminate was then pressed to reduce the thickness of the mixture layer to 45 μm and the density of the mixture layer to 2.4 g / cm. 3 Finally, the pressed laminate was cut to a diameter of 16 mm to obtain a positive electrode.
[0080] 1.1.5 Preparation of the negative electrode The Li foil was cut to a diameter of 19 mm to obtain a negative electrode.
[0081] 1.1.6 Coin cell fabrication A CR2032 coin cell was made using the above positive and negative electrodes. A PP porous separator was used as the separator, and the electrolyte was a mixture of EC (ethylene carbonate) and DMC (dimethyl carbonate) in a volume ratio of 3:7, with lithium hexafluorophosphate (LiPF6) dissolved at a concentration of 1 mol / L as the supporting electrolyte.
[0082] 1.2 Example 2 Positive electrode active material particles were prepared in the same manner as in Example 1, except that a mixed salt of GaCl3 and LiCl in a molar ratio of 1:1 was used and the temperature during ion exchange was set to 100°C. A positive electrode, a negative electrode, and a coin cell were then prepared.
[0083] 1.3 Comparative Example 1 Positive electrode active material particles were prepared in the same manner as in Example 1, except that a mixed salt of LiNO3 and LiCl in a molar ratio of 88:12 was used and the temperature during ion exchange was set to 280°C. Positive electrodes, negative electrodes, and coin cells were then prepared.
[0084] 1.4 Comparative Example 2 When preparing the precipitate (precursor particles), Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and Al(NO3)3·9H2O were weighed out so that the molar ratio of Mn, Ni, Co, and Al was 5:2:2:1. When preparing the Na-containing transition metal oxide particles having a P2 type structure, the precursor particles and Na2CO3 were mixed in a composition ratio of Na 0.67 Mn 0.5 Ni 0.2 Co 0.2 Al 0.1 Positive electrode active material particles were prepared in the same manner as in Comparative Example 1, except that a mixed powder was obtained by mixing so that the concentration of the positive electrode active material particles became O2, and a positive electrode, a negative electrode, and a coin cell were prepared using the positive electrode active material particles.
[0085] 1.5 Comparative Example 3 When preparing the precipitate (precursor particles), Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and Al(NO3)3·9H2O were weighed out so that the molar ratio of Mn, Ni, Co, and Al was 50:20:26:4. Positive electrode active material particles were prepared in the same manner as in Comparative Example 2, except that a positive electrode, a negative electrode, and a coin cell were produced.
[0086] 1.6 Comparative Example 4 When preparing the precipitate (precursor particles), Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and Ga(NO3)3·nH2O were weighed out so that the molar ratio of Mn, Ni, Co, and Ga was 50:20:27:3. Positive electrode active material particles were prepared in the same manner as in Comparative Example 2, except that a positive electrode, a negative electrode, and a coin cell were produced.
[0087] 2. Identification of the crystalline phase contained in the positive electrode active material particles X-ray diffraction measurements were performed on the positive electrode active material particles according to the examples and comparative examples, and the results shown in Fig. 4 were obtained. From Fig. 4, it can be seen that, although the positive electrode active material particles according to the examples 1 and 2 and the comparative examples 1 and 2 contain a small amount of T#2 type structure (a structure derived from the O2 type structure depending on the Li amount), they are formed only from the O2 type structure and its derived structures. Although not shown, the positive electrode active material particles according to the examples 1 and 2 and the comparative examples 1 and 2 have similar structures.
[0088] 3. Identification of the chemical composition of positive electrode active material particles The average chemical composition of each of the positive electrode active material particles according to the examples and comparative examples was determined by ICP-AES. The results are shown in Table 1 below. The compositions shown in Table 1 below are normalized so that the sum of Mn, Ni, Co, and element M (Al or Ga) is 1.00.
[0089] [Table 1]
[0090] 4. Observation of the distribution of element M (Al or Ga) in positive electrode active material particles The element distribution in the cross section of each of the positive electrode active material particles according to the examples and the comparative examples was observed by EDX. As a result, it was found that the element M is concentrated in the particle surface layer and has a shell shape in the positive electrode active material particles according to the examples 1 and 2, whereas the element M is uniformly present in the entire particle in the positive electrode active material particles according to the comparative examples 2 to 4. For reference, FIG. 5 shows an EDX element map of Al when observing the cross section of the positive electrode active material particle according to the example 1, and FIG. 6 shows an EDX element map of Al when observing the cross section of the positive electrode active material particle according to the comparative example 2. In addition, FIG. 7 shows an example of the Al concentration distribution from one surface of the particle through the center to the other surface in the EDX element map of Al of the cross section of the positive electrode active material particle according to the example 1. From the results shown in FIGS. 5 to 7, it can be seen that the element M is concentrated in the particle surface layer and has a shell shape in the positive electrode active material particles according to the example 1, whereas the element M is uniformly present in the entire particle in the positive electrode active material particles according to the comparative example 2. When the average chemical composition in the particle surface layer portion of each of the positive electrode active material particles according to Examples 1 and 2 was specified, the results shown in Table 2 below were obtained. When the average chemical composition in the particle center portion of each of the positive electrode active material particles according to Examples 1 and 2 was specified, the results shown in Table 3 below were obtained. Note that the compositions shown in Tables 2 and 3 below are standardized so that the sum of Mn, Ni, Co and element M (Al or Ga) is 1.00, as in Table 1. Meanwhile, for the positive electrode active material particles according to Comparative Examples 1 to 4, the chemical composition in the particle surface layer portion and the chemical composition in the center portion were substantially the same.
[0091] [Table 2]
[0092] [Table 3]
[0093] 5. Evaluation of initial discharge capacity and charge / discharge cycle characteristics The coin cells were measured for the initial discharge capacity and the capacity retention rate after 10 cycles when they were charged and discharged at a charge / discharge rate of 0.1 C. Charge / discharge was performed up to 4.8 V and discharged up to 2.0 V for each cycle.
[0094] 6. Evaluation of charge / discharge rate characteristics The prepared coin cells were charged at 0.1 C in a voltage range of 2.0-4.8 V in a thermostatic chamber maintained at 25°C, and then discharged at 0.1 C, 0.5 C, 1 C, or 5 C. The discharge capacity at each rate was measured and evaluated relative to the discharge capacity at 0.1 C, which was set as 100%.
[0095] 7. Evaluation Results Table 4 below shows the evaluation results for the distribution form of element M in the active material particles, the initial discharge capacity of the coin cell, the charge / discharge cycle characteristics of the coin cell, and the charge / discharge rate characteristics of the coin cell.
[0096] [Table 4]
[0097] The results shown in Tables 1 to 4 reveal the following: (1) The positive electrode active material particles according to Comparative Example 1 have a high initial discharge capacity but are inferior in cycle characteristics and rate characteristics. In Comparative Example 1, the O2 type structure becomes unstable in the high potential region of 4.8 V, which is considered to be the reason for the deterioration of the cycle characteristics and rate characteristics. (2) The positive electrode active material particles according to Comparative Example 2 have excellent cycle characteristics and rate characteristics, but have a low initial discharge capacity. In Comparative Example 2, the O2 type structure was stabilized by doping a large amount of element M into the entire surface and center parts of the particles, while the charge / discharge capacity was significantly reduced by doping a large amount of element M, which has little contribution to charge / discharge. (3) The positive electrode active material particles according to Comparative Examples 3 and 4 are not sufficient in terms of the initial discharge capacity, cycle characteristics, and rate characteristics. In Comparative Examples 3 and 4, the particle surface and center are uniformly and slightly doped with element M, but in this case, the structure stabilization effect of element M is not sufficiently ensured in the surface layer, and the charge / discharge capacity ensured by the center is reduced because element M is uniformly doped even in the center. (4) In contrast, it is found that the positive electrode active material particles according to Examples 1 and 2 are more likely to achieve both high capacity and excellent cycle characteristics than the positive electrode active materials according to Comparative Examples 1 to 4. It is also found that the positive electrode active material particles according to Examples 1 and 2 are more likely to ensure excellent rate characteristics than the positive electrode active materials according to Comparative Examples 1 to 4. It is believed that the positive electrode active material particles according to Examples 1 and 2 have element M concentrated in the surface layer of the particles, and the O2 type structure is stabilized in the surface layer of the particles, and the effect of this stabilized extends to the center. It is also believed that the molar concentration of element M in the center of the particles is relatively low, and the center ensures a large charge / discharge capacity.
[0098] 8. Supplementary Information In the above examples, the transition metal elements include all of Mn, Ni, and Co, Li, the element M, and O, but the transition metal elements constituting the positive electrode active material particles are not limited thereto. For example, when at least one element selected from Mn, Ni, and Co, Li, the element M, and O are included, the O2 type structure is easily formed.
[0099] In the above examples, the element M includes Al or Ga, but the element M constituting the positive electrode active material particles is not limited thereto. For example, when the element M includes at least one selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W, it is considered that the effect of stabilizing the O2 type structure by the element M can be obtained.
[0100] 7. Summary From the above examples, it can be said that positive electrode active material particles that (1) have an O2 type structure, (2) contain at least one element selected from Mn, Ni, and Co, Li, the element M, and O, (3) the element M is at least one element selected from B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, and W, and (4) have a higher molar concentration of the element M in the surface layer portion of the particle than the molar concentration of the element M in the center portion of the particle are likely to achieve both high capacity and excellent cycle characteristics. [Explanation of symbols]
[0101] 1 Positive electrode active material particles 1a Surface layer 1b center 10 positive electrode 11 Cathode active material layer 12 Positive electrode current collector 20 Electrolyte layer 30 negative electrode 31 Negative electrode active material layer 32 Negative electrode current collector 100 Lithium-ion secondary battery
Claims
1. Positive electrode active material particles, It has an O2 structure, Contains at least one element selected from Mn, Ni, and Co, Li, an element M, and O; The element M is at least one of Al and Ga, The particle as a whole has a chemical composition represented by Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2 (wherein 0<a≦1.00, 0≦b≦0.20, x+y+z=1, and 0<p+q+r≦0.07), the molar concentration of the element M in the surface layer of the particle is higher than the molar concentration of the element M in the center of the particle; Positive electrode active material particles.
2. The chemical composition of the surface layer is Li a Na b Mn x-s Ni y-t Co z-u M s+t+u O 2 (wherein 0<a≦1.00, 0≦b≦0.20, x+y+z=1, and 0.08<s+t+u.) The positive electrode active material particles according to claim 1 .
3. The chemical composition of the core is Li a Na b Mn x-h Ni y-i Co z-j M h+i+j O 2 (wherein 0<a≦1.00, 0≦b≦0.20, x+y+z=1, and 0≦h+i+j<0.07). The positive electrode active material particles according to claim 2 .
4. A method for producing positive electrode active material particles, comprising: Obtaining Na-containing transition metal oxide particles having a P2 type structure, and At least a part of Na in the Na-containing transition metal oxide particles is ion-exchanged with Li, and an element M which is at least one of Al and Ga is doped into the particle surface layer to obtain Li-containing transition metal oxide particles having an O2 type structure; A manufacturing method comprising:
5. a salt containing Li and the element M is brought into contact with the Na-containing transition metal oxide particles, thereby ion-exchanging at least a part of Na in the Na-containing transition metal oxide particles with Li and doping the element M into the particle surface layer; The method according to claim 4.
6. The salt is a salt containing Li, the element M, and a halogen; The method according to claim 5 .
7. The Na-containing transition metal oxide particles are c Mn x Ni y Co z O 2 (wherein 0<c≦1.00, x+y+z=1), The method according to any one of claims 4 to 6.
8. A lithium ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode, The positive electrode comprises the positive electrode active material particles according to any one of claims 1 to 3. Lithium-ion secondary battery.
Citation Information
Patent Citations
Cathode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery using the same, and method of manufacturint cathode active material for nonaqueous electrolyte secondary battery
JP2010092824A
Positive electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery arranged by use thereof
JP2014186937A
Method for producing positive electrode active material and method for manufacturing lithium ion battery
JP2021068556A
Method for manufacturing positive electrode active material, positive electrode active material, and method for manufacturing lithium ion battery
JP2022078776A
Positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
WO2013108571A1